Pemanfaatan TikTok sebagai Media Microlearning untuk Mengelola Cognitive Load dalam Pembelajaran Daring - Dyah Ayu Sulistyaming Cipta; Dedi Kuswandi; Ika Andrini Farida (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2025)
Abstract: Online learning in higher education often faces the problem of increasing students’ cognitive load due to poorly structured and excessive material presentation. One potential strategy to address this issue is microlearning. This study aims to analyze the use of TikTok as a microlearning medium in managing students’ cognitive load in online learning. The research employed a descriptive quantitative approach conducted in the Design and Innovation of Learning course within the Mathematics Education Study Program at Universitas Insan Budi Utomo during the odd semester of the 2025/2026 academic year, involving 41 students. Learning was carried out over six sessions using TikTok-based microlearning curated through Padlet. Data were collected using a cognitive load questionnaire covering intrinsic, extraneous, and germane cognitive load, and then analyzed descriptively. The results show that intrinsic cognitive load was at a moderate level, extraneous cognitive load was at a low level, and germane cognitive load was at a high level. These findings indicate that TikTok-based microlearning can reduce irrelevant cognitive load while simultaneously fostering students’ understanding processes in online learning.   Keywords: Microlearning; TikTok; Cognitive Load; Online Learning; Educational Psychology